Stable mode-locked operation with high temperature characteristics of a two-section InGaAs/GaAs double quantum wells laser - Qiao, Zhongliang (2021)
A monolithic two-section InGaAs/GaAs double quantum wells (DQWs) mode-locked laser (MLL) emitting at 1.06~μ \text{m} is demonstrated. Stable mode locking operation is achieved up to 80 °C. The fundamental repetition rate is at 9.51 GHz with a signal-to-noise ratio (SNR) of more than 55 dB, and up to the fourth harmonic at 38.04 GHz is observed. The characteristic temperature ( T_{0} ) of the laser and the influences of absorber bias voltage on T_{0} have been systematically investigated. From our findings, T_{0} shows a two-segment feature, and is slightly affected by the absorber bias voltage for photon saturation.